Soil nutrient improvement with organic amendments: a basis for lemon orchard management - Raushanfikr Bushron; Atiqah Aulia Hanuf; Alfian Tri Yulianto; M. Wasilul Lutfi; Dinda Mahartian Yunita; Retno Suntari; Soemarno Soemarno (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Lemon trees require the nutrients they extract from the soil. This research aims to analyze the impact of organic matter application on enhancing soil nutrient availability and improving soil chemical properties using a pot-scale incubation experiment. This study used a completely randomized design with eight treatments and four replications. The pot treatment used 10 kg of air-dry soil per pot mixed with an organic matter dosage of 30 tons ha-1 and was observed at 2, 4, 8 weeks after applications. The treatment consisted of P1 (topsoil, control), P2 (subsoil, control), P3 (topsoil + compost), P4 (subsoil + compost), P5 (topsoil + cow manure), P6 (subsoil + cow manure), P7 (topsoil + goat manure), and P8 (subsoil + goat manure). The results indicated that compost and manure fertilizer had a significant effect in increasing soil chemical properties (pH, organic carbon content, cation exchange capacity, total-N, available-P, and exchangeable-K), with topsoil treatment having the highest value compared to the subsoil treatment, almost at all parameters. The topsoil treatment + 30 tons ha⁻¹ cow manure significantly increased the N-total by 44.44% at 8 and 12 WAA on the control treatment. The topsoil treatment + goat manure 30 tons ha-1 significantly increased P-available by 13.63 - 29.74% and exchangeable-K by 40.61 - 62.88% at 4, 8, and 12 WAA against the control treatment. Based on these findings, the best fertilizer method of topsoil treatment + 30 tons ha⁻¹ of manure is recommended to increase the soil fertility of the lemon tree soil.